COMPARISON OF ALGEBRA LEARNING OUTCOMES USING REALISTIC MATHEMATICS EDUCATION (RME), TEAM ASSISTED INDIVIDUALIZATION (TAI) AND CONVENTIONAL LEARNING MODELS IN JUNIOR HIGH SCHOOL 1 MASOHI - Anderson Leonardo Palinussa (IKIP Siliwangi and I-MES, 2020)
The study aims to examine the application of the Realistic Mathematics Education (RME), the Cooperative Learning Model Team Assited Individualization (TAI) type and conventional learning models on algebra. The population in thIS study were all eighth grade SMPN 1 Masohi. The type of this study is an experimental research design with quasi experimental research. Instruments in this study using the test results, analyzed using ANOVA test and further tests using Tukey's HSD test. From the analysis of these study obtained data: (1) Based on the normality test results obtained sig. X1 (RME Learning Model) of 0.976, X2 (Cooperative Learning Model TAI Type) of 0.889 and X3 (Conventional Learning Model) of 0.906. (2) Based on the one-way ANOVA calculation with the SPSS 20.0 program, obtained a significance value of 0.003. (3) There are significant differences in algebra learning outcomes between classes using the RME learning model, the cooperative learning model TAI type and conventional learning model, and (4) The algebra learning outcomes of students used the RME learning model are higher than the students that are used cooperative learning models TAI type and the students that used conventional learning model.